Pentingnya Kompetensi Sosial Bagi Guru PAK Profesional - Debora Sitohang; Elisamark Sitopu (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Competence means the ability needed to do or carry out work based on knowledge, skills and attitudes. Social competence is one of the five competencies that must be possessed by a Christian Religious Education Teacher. A teacher's social competence is seen from his ability to communicate and interact with students, fellow educators, parents and the community. The importance of social competence for a professional Christian Religious Education Teacher is to build positive relationships with students, create collaboration with fellow educators, build communication with parents as well as with the surrounding community and the whole form of the relationship is as an effort from an educator in understanding others. Creating and maintaining good social relationships means that it contains care and empathy as taught by Jesus as Great Master so that everyone not only pays attention to their own interests but also the interests of others including the interests of students.